Subjective Well-Being Pada Penyandang Tunadaksa - Aini, Afifah Nur, Dra. Zahrotul Uyun, M. Si (2017)
Subjective well-being is happiness in someone's life and life satisfaction on the individual. Happiness at the individual based on the emotional state of the individual and how the individual perceives himself and his world. quadriplegic can be defined as people with deformities or defects in the system of muscles, bones and joints that can lead to impaired coordination, communication, adaptation, mobilization, and impaired development of personal integrity. This study used a qualitative approach, method of data collection is by interview with five quadriplegic informants withquadriplegic. Analysis of the data used in this research is thematic analysis. The purpose of this study was to describe the subjective well being in quadriplegic. The results of this study are a happy feeling arises when the informant can gather with family, friends, and those feelings of happiness not only for the material things, because happiness comes from the heart. Most informants still feel not satisfied because they have not been able mendaptkan what they want like, mengejajar ideals - ideals, and can be accomplished. But the informant had been satisfied because it does not depend on the parents about material things. , The embarrassment was caused by the condition a different subject that makes some subjects are not confident, feel insecure and embarrassed to travel far. However, there are some subjects that already feel ordinary with the current condition of the subject